Actitudes y conocimientos del personal de enfermería del Hospital General Isidro Ayora de la ciudad de Loja sobre el paciente con VIH/SIDA. - Díaz Agila, Diego Andrés (2017)
SUMMARY The Human Immunodeficiency Virus (HIV) infects the cells of the immune system, altering or canceling out its function, causing a progressive deterioration of the immune system, with an "immunodeficiency". Acquired Immunodeficiency Syndrome (AIDS) represents the most advanced stage of HIV. The World Health Organization indicates that in 2014 1.2 million people died of a cause of HIV worldwide. In Ecuador, according to data from the National Institute of Statistics and Census in 2014, 828 deaths were recorded and 3147 infected patients were registered. Given the HIV / AIDS figures, it is considered a global public health problem and health personnel should be ready for the treatment of the disease, and it is for this reason that research on the attitudes and knowledge of the staff Of the General Hospital "Isidro Ayora" of the city of Loja on the patient with HIV / AIDS. This study has a quantitative, descriptive and cross-sectional approach. The sample corresponds to 93 nurses and nurses, the CAP questionnaire (Knowledge, Attitudes and Practices) was applied. In this study it was concluded that nurses have a very good knowledge in the transmission of the disease (97.85%), there is a misconception about the probability of contagion in health personnel (70.97%). In terms of attitudes, the staff has positive attitudes towards acceptance and willingness to provide care to patients with HIV diagnosis (more than 90%). Negative attitudes are due to the concern of becoming infected with the disease, becoming nervous during the care of the patient. KEY WORDS: Attitudes, knowledge, Nursing staff, people living with HIV/AIDS.